Institutos federais de educação, ciência e tecnologia: contexto de influência, produção de texto e tensões, na construção da política pública, relativa ao processo de criação dos Institutos federais - Figueiredo, Amilton de Moura (Universidade do Vale do Rio dos Sinos, 2019)
The present thesis has as study object the influence context, the text production and tensions, in a public politic creation, related to Institutos Federais de Educação, Ciência e Tecnologia (Federal Institutes of Education, Science and Technology – IF’s) creation process. The general objective was identify fundamental elements and discuss about corresponding process in the influence context, at the text production and tensions in public politic creation, related to Institutos Federais de Educação, Ciência e Tecnologia (Federals Institutes of Education, Science and Technology) creation process. From this orientation, specific objectives were: describe historical and political conjuncture of the period when IF’s project was conceived; identify actors and interests intervening in the debates that preceded IF’s creation; understand factors related to influences, objectives and purposes of IF’s creation; verify basic elements of creation law of IF’s writing (Law No. 11.892 / 08); and investigate main disputes around policy creation of IF’s text. The thesis was produced from a qualitative study, whose investigative path was based on policy cycle approach, combined with Critical Theory. In methodological terms, besides bibliographic survey, for constitution of the theoretical referential, a documental analysis was carried out, involving laws, decrees and normative acts, as well as semi-structured interviews, with main actors involved representation. An analysis of bill legislative process for the IF’s was conducted, in addition to government and union documents analysis, which made it possible to identify the set of prominent tensions, during the policy construction, demonstrating the influences on guideline construction and conception. The study indicated that public policies are built in tensioned environments and are susceptible to the influences of different interest groups that orbit surrounding. It make’s possible to identify agendas referring to each actor and interest group represented in the process, as well has brought on the surface disputes over new institutionally, which, with new tasks and administrative reorganization, reshaped already established power structures. The influence of legislators, who sought meet interests of union, government and their constituencies, was also attested, demonstrating that policies are a living and dynamic process in all contexts. In this sense, it was observed that the government, union, councils and legislative had divergent views about the new institutionally proposed. The necessary opposition and conflicts legitimized public policy, showing that influences, demonstrating that influences drove the direction of proposal under discussion and that the virtuous process conferred the relevance of IF’s, as an action of social inclusion and citizenship.
Keywords: Institutos Federais; Políticas Públicas Educacionais; Educação Profissional; Ciclo de Políticas; Federal Institutes; Public Educational Policies; Professional Education; Policy Cycle; ACCNPQ::Ciências Humanas::Educação